An Analysis of Countercyclical Policies of The FHLBB - KENT, RICHARD J. (Journal of Finance, 1981)
ABSTRACT Three policies of the Federal Home Loan Bank Board, the Specially Priced Advances Program in 1970–1, a program of advances at a reduced interest rate in 1974, and changes in the minimum liquidity ratio, are analyzed. A model of portfolio allocation is developed and estimated for savings and loan associations. Most of the net increase in advances borrowed under the first two programs have not been lent in the mortgage market. Reductions in the minimum liquidity requirement have resulted in an increase in mortgage lending, but substantial effects are not felt until a year after the liquidity requirement is reduced.